2009
DOI: 10.1016/j.nuclphysb.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic charge lattices, moduli spaces and fusion rules

Abstract: We analyze the set of magnetic charges carried by smooth BPS monopoles in Yang-MillsHiggs theory with arbitrary gauge group G spontaneously broken to a subgroup H. The charges are restricted by a generalized Dirac quantization condition and by an inequality due to Murray. Geometrically, the set of allowed charges is a solid cone in the coroot lattice of G, which we call the Murray cone. We argue that magnetic charge sectors correspond to points in the Murray cone divided by the Weyl group of H; hence magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…It has been proven that these are also necessary conditions for finite energy when the gauge group is SU (2) [14], and this is expected to be true in general [41,49]. (See also the discussion in [50].) When 't Hooft defects are present there are certain boundary terms that should be included in the energy functional.…”
Section: Boundary Terms Finite Energy and Boundary Conditionsmentioning
confidence: 99%
“…It has been proven that these are also necessary conditions for finite energy when the gauge group is SU (2) [14], and this is expected to be true in general [41,49]. (See also the discussion in [50].) When 't Hooft defects are present there are certain boundary terms that should be included in the energy functional.…”
Section: Boundary Terms Finite Energy and Boundary Conditionsmentioning
confidence: 99%
“…It is important to notice that the electric orbit is non-trivially fibered on the magnetic one. This fact is related to the difficulties to associate to non-Abelian monopoles well-defined algebraic objects, as required by quantum mechanics [21,48].…”
Section: Rational Map Construction For the Monopole Moduli Spacementioning
confidence: 99%
“…Using the identification of singular monopoles with 't Hooft operators and computing the operator product expansion (OPE) for the latter, they showed that the fusion rules of purely magnetic monopoles are identical to the fusion rules of the dual gauge group. It was shown in [7] that in an ordinary N = 4 Yang-Mills theory, the classical fusion rules of monopoles, obtained from patching together monopole solutions to the classical field equations, are also consistent with the non-abelian Montonen-Olive conjecture.…”
Section: Jhep01(2010)095mentioning
confidence: 76%
“…The original treatment of that condition in [1,2] makes use of the identification between t * and t via the Killling form and uses a basis in order to describe both magnetic and electric charges as r-component vectors. We have followed that path in the current paper, and also in [7] where we give a review using the same conventions as in the current paper. It is worth emphasising, however, that the Dirac condition only requires the natural duality between t (magnetic charges) and t * (electric charges) for its formulation, as emphasised in [15].…”
Section: Magnetic Charge Latticesmentioning
confidence: 99%